Partial Invasive Mole with Bilateral Torsion of Theca Lutein Cysts - Yadav, Randhir Sagar; Shrestha, Shumneva; Sharma, Santosh; Singh, Meeta; Bista, Kesang Diki; Ojha, Neebha (Journal of Nepal Health Research Council, 2018)
Gestational trophoblastic neoplasia is extremely rare entity accounting 1% of all gynecological malignancies. Invasive mole is a form of Gestational trophoblastic neoplasia which is locally invasive with propensity of metastasis. Association of partial mole with invasive mole and/or theca lutein cysts is a rare occurrence. Large cysts may present with complications. A case with these rare combinations presented at 15+3 weeks period of gestation as acute abdomen due to torsion of bilateral theca lutein cysts is reported. Right salpingo-ophorectomy with untwisting of left cyst was done. Six cycles of chemotherapy was given with regular βhCG monitoring. First trimester dating scan would have helped in early diagnosis, treatment and prevention of complications. Keywords: Invasive mole; theca lutein cysts; torsion.